Quality of ADL task performance in persons with schizophrenia: Looking beyond independence. - Nielsen, Kristina Tomra; Andersen, Ulla; Wæhrens, Eva Ejlersen; von Bülow, Cecilie (Scandinavian Journal of Occupational Therapy, 2023)
Persons with schizophrenia may experience decreased ability to perform activities of daily living (ADL) indicated by need for assistance in everyday life. Others are independent, but their quality of ADL task performance in terms of effort and efficiency may still be impacted. The overall purpose of this study was to explore the quality of ADL task performance in subgroups with schizophrenia (independent/needing assistance). Participants were in- and outpatients at a Psychiatric Hospital diagnosed with schizophrenia (n = 83). Their quality of ADL task performance was evaluated using the Assessment of Motor and Process Skills (AMPS). Evaluations were conducted at the hospital. Two subgroups (A: independent and B: needing assistance) were created based on AMPS ADL ability measures. The majority in both subgroups had AMPS ADL ability measures within the risk zones. Further, the majority in subgroup A had ADL ability measures within age expectations but below mean for well persons of the same age. Both ineffective motor and process skills were identified in both subgroups Occupational therapy is indicated for persons with schizophrenia, both for independent persons and for persons needing assistance. This is to prevent decline in or to enhance ADL ability.